ANALISIS PUISI “MESIN RIWAYAT” KARYA HERI ISNAINI DENGAN PENDEKATAN SEMIOTIKA - Siti Maryam (IKIP Siliwangi, 2020)
The aim of this study is to describe the poem of the machine's chronicle of Heri Isnaini using a semiotics approach. The focus of discussion of this article is the aspect of the mark that appears throughout the poem and is analysed so that it can represent the mark of the poem. The study is on the background because the author is interested in analyzing the poem, because the content in the poem tells of the wheel of life and destination that become the downstream of each human journey. Analysis in this study uses descriptive methods. A descriptive method is research that attempts to describe a symptom, an event occurring at the present time or an actual problem. Analyzing the data in the study: (1) selecting poetry and reading machine poems by Heri Isnaini's history, (2) analyzing the poem using a semiotics approach, (3) describing the meaning of the poem. Research shows that this poem refers to something textually and has textual meaning to the text for the reader to know, that is, to illustrate it as the time humans go through life. Human existence is inherent in its relation to space and time. Reality shows that the dimensions of space and time are the affirmation of human existence. Human identity is partly determined by its perception of time, that is, how humans perceive and treat time symbolically in life. This poem, therefore, is especially meaningful to read by both young and adults because it has meaningful words that resonate with real life.